2019
DOI: 10.1002/anie.201814653
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Healing Integrated All‐in‐One Zinc‐Ion Battery

Abstract: The self‐healing of zinc‐ion batteries (ZIBs) will not only significantly improve the durability and extend the lifetime of devices, but also decrease electronic waste and economic cost. A poly(vinyl alcohol)/zinc trifluoromethanesulfonate (PVA/Zn(CF3SO3)2) hydrogel electrolyte was fabricated by a facile freeze/thaw strategy. PVA/Zn(CF3SO3)2 hydrogels possess excellent ionic conductivity and stable electrochemical performance. Such hydrogel electrolytes can autonomously self‐heal by hydrogen bonding without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
264
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 354 publications
(267 citation statements)
references
References 49 publications
(30 reference statements)
2
264
0
1
Order By: Relevance
“…Reproduced with permission from ref. . d) Optical images showing that the chemical cross‐linked PAM hydrogel with good stretchability (3000 % strain).…”
Section: Multifunctional Hydrogel Electrolytesmentioning
confidence: 99%
“…Reproduced with permission from ref. . d) Optical images showing that the chemical cross‐linked PAM hydrogel with good stretchability (3000 % strain).…”
Section: Multifunctional Hydrogel Electrolytesmentioning
confidence: 99%
“…By removing substrate as a parameter, we witnessed an unprecedented freedom for multiple device integration and new architectures. The GPAH electrolyte also exhibited temporary spontaneous interface healing properties for a few hours after gelation . If the device is folded on itself during this period, then it retained remarkable electrochemical performance while healing the interface between the overlapped GPAH.…”
Section: Resultsmentioning
confidence: 99%
“…The GPAH electrolyte also exhibited temporary spontaneous interface healing properties for a few hours after gelation. [39] If the device is folded on itself during this period, then it retained remarkable electrochemical performance while healing the interface between the overlapped GPAH. This effectively means shorter transport paths for ions between different region of the microelectrodes.…”
Section: Advantages Of Hydrogel Electrolytementioning
confidence: 99%
“…The addition of zinc salts into PVA‐based electrolyte can lead to a favorable phenomenon that the electrolyte can self‐healed after being destroyed, which is important for the practical application of flexible energy storage devices. A ZIB based on the poly(vinyl alcohol)/zinc trifluoromethanesulfonate (PVA/Zn(CF 3 SO 3 ) 2 ) hydrogel electrolyte was reported by Huang et al,102 as shown in Figure 8c. The battery is fabricated by a facile freeze/thaw strategy utilizing polyaniline (PANI) nanorods as cathode and Zn as anode, together with PVA/Zn(CF 3 SO 3 ) 2 as electrolyte and separator (Figure 8d).…”
Section: Recent Progress Of Polymer Electrolytes For Zibsmentioning
confidence: 99%
“…f) Illustration of structure for the self‐healing integrated all‐in‐one ZIBs and LEDs powered by this battery. Reproduced with permission 102. Copyright 2019, Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Recent Progress Of Polymer Electrolytes For Zibsmentioning
confidence: 99%